(untitled) (Global Journal of Medical Research, 2020)
Reported case was a 68 years old Male with Earlystage Osteoarthritis of both knees Sandhigata Vata accompanied by reduced medial joint spaces bilaterally marginal osteophytes Initially VAS scale rating was poor Proven herbal formulations like Painmukti MJ Painmukti Sandhical Painmukti cream along with Advance Virechana Arthrox Knee Dhara Yogbasti and Matrabastitwice a week was given for 16months Visual analog scale for knee pain and an Ayurveda clinical assessment criteria used to evaluate the effects of Treatment and Herbal remedies monthly basis After a treatment of 30 days of Advance Virechana Arthrox Knee Dharaand Yogbasti Pain movement and stability of the joint was improved at an excellent level During follow up visit with the help of Matrabasti twice a week Pain movement of joint and stability and even X-ray reading were change In conclusion this knee osteoarthritis patient s quality of life improved by Advance Virechana Arthrox